Hubungan Kompetensi dengan Kinerja Pada Tenaga Kependidikan di Universitas Islam Bandung - Kamalia Aurananda Ikhsan; Aminuddin Irfani (Bandung Conference Series: Business and Management, 2022)
Abstract. A good organization is an organization that can pay attention to its employees, because the success of the organization is very dependent on the performance of the employees in it. Performance as a measure of how human resources in an organization have played a good role in the progress of the organization. If employees want to produce good performance, it is necessary to have competencies that are in accordance with their fields in a company. Competence is a person's ability to carry out his work. Therefore, the author in this case examines the competence and performance of educational staff, as well as the relationship between the two at the Bandung Islamic University through primary and secondary data that has been obtained. The hypothesis of this study is that there is a positive relationship between competence and work performance of education staff at the Islamic University of Bandung. Based on the research results, the relationship between competence and the performance of education personnel at the Islamic University of Bandung has a strong and positive relationship. This means that the higher the competence of the Bandung Islamic University education staff, the higher the performance of the educational staff. So the hypothesis H1 which reads that competence has a relationship with performance is accepted, while Ho which reads that competence has no positive relationship with performance is rejected. So, it can be concluded that there is a positive relationship between competence and performance in the education staff of the Islamic University of Bandung. Keywords: Competence, Performance Abstrak. Organisasi yang baik adalah organisasi yang dapat memperhatikan karyawannya, karena ke sukses-an organisasi sangat bergantung pada kinerja karyawan yang ada di dalamnya. Kinerja sebagai bentuk ukuran bagaimana sumber daya manusia yang ada didalam suatu organisasi sudah berperan dengan baik terhadap kemajuan organisasinya. Jika karyawan ingin menghasilkan kinerja yang baik, diperlukan adanya kompetensi yang sesuai dengan bidangnya di suatu perusahaan. Kompetensi merupakan kemampuan seseorang dalam melaksanakan pekerjaannya. Oleh karena itu penulis dalam hal ini meneliti kompetensi dan kinerja tenaga kpeendidikan, serta hubungan antara keduanya pada Universita Islam Bandung melalui data primer dan sekunder yang telah didapat. Adapun hipotesis dari penelitian ini adalah terdapat hubunganyang positif antara kompetensi dengan kinerja kerja tenaga kependidikan pada Universitas Islam Bandung. Berdasarkan hasil penelitian hubungan antara kompetensi dengan kinerja tenaga kependidikan pada Universitas Islam Bandung memiliki hubungan yang kuat dan positif. Hal ini berarti semakin tinggi kompetensi yang dimiliki tenaga kependidikan Universitas Islam Bandung, maka semakin tinggi juga kinerja tenaga kependidikannya. Sehingga hipotesis H1 yang berbunyi kompetensi memiliki hubungan dengan kinerja diterima, sedangkan Ho yang berbunyi kompetensi tidak memiliki hubungan positif dengan kinerja ditolak. Maka, dapat disimpulkan bahwa adanya hubungan positif antara kompetensi dengan kinerja pada tenaga kependidikan Universitas Islam Bandung. Kata Kunci : Kompetensi, Kinerja